Kalkipyrone B, a marine cyanobacterial γ-pyrone possessing cytotoxic and anti-fungal activities. (February 2016) - Bertin, Matthew J.; Demirkiran, Ozlem; Navarro, Gabriel; Moss, Nathan A.; Lee, John; Goldgof, Gregory M.; Vigil, Edgar; Winzeler, Elizabeth A.; Valeriote, Fred A.; Gerwick, William H.
Graphical abstract: Bioassay-guided fractionation of the lipophilic extract of a field collection of cyanobacteria from American Samoa resulted in the isolation and structure characterization of kalkipyrone B. Highlights: Bioassay guided isolation gave three γ-pyrones from a marine cyanobacterium. Kalkipyrone B was determined by NMR and Mosher's ester analysis. Kalkipyrone A was cytotoxic while kalkipyrone A and B were equipotent antifungals. 16S rRNA analysis identified the producing strain to be a Leptolyngbya species. Abstract: Bioassay-guided fractionation of two marine cyanobacterial extracts using the H-460 human lung cancer cell line and the OVC-5 human ovarian cancer cell line led to the isolation of three related α-methoxy- β, β ′-dimethyl-γ-pyrones each containing a modified alkyl chain, one of which was identified as the previously reported kalkipyrone and designated kalkipyrone A. The second compound was an analog designated kalkipyrone B. The third was identified as the recently reported yoshinone A, also isolated from a marine cyanobacterium. Kalkipyrone A and B were obtained from a field-collection of the cyanobacterium Leptolyngbya sp. from Fagasa Bay, American Samoa, while yoshinone A was isolated from a field-collection of cyanobacteria (cf. Schizothrix sp.) from Panama. One-dimensional and two-dimensional NMR experiments were used to determine the overall structures and relative configurations of the kalkipyrones, and the absolute configuration of kalkipyrone B was determined by 1 H NMR analysis of diastereomeric Mosher's esters. Kalkipyrone A showed good cytotoxicity to H-460 human lung cancer cells (EC50  = 0.9 μM), while kalkipyrone B and yoshinone A were less active (EC50  = 9.0 μM and >10 μM, respectively). Both kalkipyrone A and B showed moderate toxicity to Saccharomyces cerevisiae ABC16-Monster strain (IC50  = 14.6 and 13.4 μM, respectively), whereas yoshinone A was of low toxicity to this yeast strain (IC50  = 63.8 μM).